Effect of methane augmentation on combustion stability and unregulated emissions in compression ignition engine. (1st March 2020) - Tripathi, Gaurav; Sharma, Priybrat; Dhar, Atul
Highlights: Methane port fuel injection in compression ignition engine with direct injection of diesel. Combustion characteristics and stability of methane diesel dual fuel engine. Effect of methane supplementation on unregulated emissions (Aldehydes and Aromatics). Abstract: The replacement of conventional diesel fuel in CI engines is being attempted by various researchers to solve the problem of the regulated and unregulated engine emissions and diesel scarcity. Additionally, stringent emission norms are motivating to find replacement of diesel with clean and sustainable alternative fuels. In last few decades, the demand of natural gas has increased drastically and it emerged as promising clean and economic energy source for transport. Therefore, the current investigation focuses on methane-diesel dual fuel combustion in single cylinder water cooled diesel engine at rated rpm of 1500. The experiment was performed at different loads (25, 50 and 75%) with varying methane supplementation. The higher methane energy share at lower and higher load conditions were reported as challenging engine operating conditions by various researchers. Therefore, present work explores the effect of higher energy substitution of methane at lower and higher load conditions. At these operating conditions, combustion stability was characterised by coefficient of variation in peak pressure and mean cylinder pressure. The study investigates the combustion stability of methane-diesel dual fuel engine through cycle to cycle variability and peak pressure location variation. Subsequently, the effect of addition of methane were also investigated on unregulated emissions like aldehydes and aromatics, which are reported carcinogens and act as precursors in particulate matter formation. Overall, methane energy share reduces the COV at higher loads and the unregulated emissions at all load conditions.